PLAYAS Y MANEJO APTITUD RECREATIVA EN PLAYAS TURÍSITICAS DE MANZANILLO, COLIMA, MÉXICO - Silva-Iñiguez, L.; Gutiérrez-Corona, C.G.; Pérez-López, R.; Sosa-Avalos, R.; López-Magaña, S.A. (European Scientific Journal, ESJ, 2014)
Coastal areas, in particular the beaches are natural sites visited by tourists and population. The beaches are so important in the productive processes in each region specially, the role it plays in the socioeconomic development of the coastal tourist town; make it necessary to ensure its permanence in conditions that satisfy the demands and expectations of users. In other words, the beaches would be quality. Therefore, the objective of this job is to evaluate the variation of the recreational aptitude in Manzanillo, Colima beaches, with bases of aesthetic quality, bacteriology and biophysical attributes. We evaluated 16 different activities in the emerged and submerged zones of six beaches localized in the bays every two months. San Pedrito beach presented the major annual recreational aptitude, resulting suitable for 11 activities. In the Santiago bay, Miramar beach north zone resulted suitable for 12 activities. Salagua located in the Manzanillo bay showed the worst recreational quality.